Idealization in Lapači prachu by Lucie Faulerová - Roháčová, Tereza (Bohemica Olomucensia, 2020)
The study focuses on the novelistic debut of Lucie Faulerová Lapači prachu. The primary goal is to describe the relationship of the protagonist Anna and her sister Dana to idealization or rather de-idealization of the family, partnerhood and womanhood, and to find out where this tendency for a positive or negative view of life stems. The secondary endeavor was to find sings of unreliable narration.
Keywords: Lucie Faulerová; Lapači prachu; idealization; de-idealization; unreliable narration